The dark side of silicon : energy efficient computing in the dark silicon era - Rahmani, Amir M.; Liljeberg, Pasi; Hemani, Ahmed; Jantsch, Axel; Tenhunen, Hannu (Springer, 2017)
This book presents the state-of-the art of one of the main concerns with microprocessors today, a phenomenon known as "dark silicon". Readers will learn how power constraints (both leakage and dynamic power) limit the extent to which large portions of a chip can be powered up at a given time, i.e. how much actual performance and functionality the microprocessor can provide. The authors describe their research toward the future of microprocessor development in the dark silicon era, covering a variety of important aspects of dark silicon-aware architectures including design, management, reliability, and test. Readers will benefit from specific recommendations for mitigating the dark silicon phenomenon, including energy-efficient, dedicated solutions and technologies to maximize the utilization and reliability of microprocessors. Enables readers to understand the dark silicon phenomenon and why it has emerged, including detailed analysis of its impacts; Presents state-of-the-art research, as well as tools for mitigating the dark silicon phenomenon; Includes coverage of various aspects of dark silicon awareness in design, management, reliability, and tests.- Resumé vydavatel
Keywords: mikroprocesory; elektronické obvody; microprocessors; electronic circuits; tmavý křemík; elektronické knihy; sborníky; electronic books; papers of several authors